Baseline radiographic osteoarthritis and semi-quantitatively assessed meniscal damage and extrusion and cartilage damage on MRI is related to quantitatively defined cartilage thickness loss in knee osteoarthritis: the Multicenter Osteoarthritis Study. Issue 12 (December 2015) - Guermazi, A.; Eckstein, F.; Hayashi, D.; Roemer, F.W.; Wirth, W.; Yang, T.; Niu, J.; Sharma, L.; Nevitt, M.C.; Lewis, C.E.; Torner, J.; Felson, D.T.
Summary: Objectives: To provide a comprehensive simultaneous relation of various semiquantitative knee OA MRI features as well as the presence of baseline radiographic osteoarthritis (OA) to quantitative longitudinal cartilage loss. Methods: We studied Multicenter OA Study (MOST) participants from a longitudinal observational study that included quantitative MRI measurement of cartilage thickness. These subjects also had Whole Organ MRI Score (WORMS) scoring of cartilage damage, bone marrow lesions (BMLs), meniscal pathology, and synovitis, as well as baseline radiographic evaluation for Kellgren and Lawrence (KL) grading. Knee compartments were classified as progressors when exceeding thresholds of measurement variability in normal knees. All potential risk factors of cartilage loss were dichotomized into "present" (score ≥2 for cartilage, ≥1 for others) or "absent". Differences in baseline scores of ipsi-compartmental risk factors were compared between progressor and non-progressor knees by multivariable logistic regression, adjusting for age, sex, body mass index, alignment axis (degrees) and baseline KL grade. Odds ratios (OR) and 95% CIs were calculated for medial femorotibial compartment (MFTC) and lateral femorotibial compartment (LFTC) cartilage loss. Cartilage loss across both compartments was studied using Generalized Estimating Equations. Results: 196 knees of 196 participants were included (age 59.8 ± 6.3 years [mean ± SD], BMI 29.5 ± 4.6, 62% women). For combined analyses of MFTC and LFTC, baseline factors related to cartilage loss were radiographic OA (KL grade ≥2: aOR 4.8 [2.4–9.5], cartilage damage (aOR 2.3 [1.2–4.4])), meniscal damage (aOR 3.9 [2.1–7.4]) and extrusion (aOR 2.9 [1.6–5.3]), all in the ipsilateral compartment, but not BMLs or synovitis. Conclusion: Baseline radiographic OA and semiquantitatively (SQ) assessed MRI-detected cartilage damage, meniscal damage and extrusion, but not BMLs or synovitis is related to quantitatively measured ipsi-compartmental cartilage thinning over 30 months.